MODERN PSYCHOLOGICAL AND PEDAGOGICAL REQUIREMENTS TO THE TEACHER OF HIGHER MEDICAL EDUCATIONAL AGENCY - Boychuk, Alexandra (Educological discourse, 2018)
The author outlines modern psychological and pedagogical requirements for a teacher of a higher medical school. The basic directions of activity of the teacher of medical university are revealed: educational, methodical, scientific and organizational activity. Its main functions are outlined: production of medical and other scientific knowledge; realization of educational process in the higher medical school on the basis of various educational and pedagogical technologies; distribution of medical knowledge; formation of the ability and awareness of the need for education throughout the life of a student at a higher medical school. The relationship between the directions and functions of the teacher is proved. It is noted that for the successful implementation of educational reforms, the teacher must have a special psychological and pedagogical training, have professional knowledge of the disciplines that he teaches to students. The need to take into account the traditions that have developed in the system of public health care in general, the specifics of medical education itself, modern changes and transformations. The complex of personal and professional characteristics of the teacher of the higher medical school is outlined. Personal qualities of the teacher include moral and ethical: empathy, concreteness, initiative, openness and sincerity, perception of feeling, politeness, respect for others, tactfulness, attentiveness, observation, sociability, accessibility, ability to win the confidence of students, curiosity, creativity, erudition. The components of the teacher’s general and professional culture are described. Common cultural requirements include tact, attentiveness, tolerance, dedication, benevolence, sense of humor, ability to support others, master your emotions, correct behavior. It is noted that professional culture implies the formation of emotional stability; endurance and self-control; possession of the skills and abilities necessary for professional activity; self-sustainability and self-confidence; independence in making decisions.